2006: the value of pelvic and femoral osteotomies in hip surgery - Pogliacomi, F.; De Filippo, M.; Costantino, et al., C. (Acta Biomedica Atenei Parmensis, 2007)
Hip problems are frequent and can represent a therapeutic challenge for the orthopaedic surgeon. In the wide spectrum of hip pathologies, coxarthrosis still remains the most common cause of hip disability. The treatment of hip disorders in adult patients has rapidly evolved during the past decades because of the enhanced understanding of osteoarthritis (OA) aetiology combined with improved imaging, better patient selection and refinements in surgical procedures. Despite great strides that have been made in the field of total hip arthroplasty (THA), femoral and pelvic osteotomy still play a successful role in the prevention and treatment of OA. Primary OA is rare, or may not exist at all, and the majority of cases that are considered as primary are secondary to a pre-existing anatomical deformity. If an identifiable anatomic and biomechanical hip abnormality is diagnosed, its surgical correction may prevent or lessen OA and postpone THA for many years or even indefinitely in certain cases. The success of such surgery depends on the correct indication, time of surgery, completeness with which osteotomies normalize the environment of the hip, and the grade of OA present when procedure is performed.